Construction of multiscale hierarchical porous titanium scaffolds and in vitro evaluation of osteogenic differentiation - QingLian Yang; Lan Wang; WenHao Zhou; JinYang Ge; XiaoTong Lu; HanYuan Liu; Sen Yu (Materials & Design)
The multiscale hierarchical porous titanium scaffolds significantly improve biomechanical adaptation and biological activity by simulating bone structure, presenting attractive application prospects. To achieve the controllable preparation of multiscale hierarchical porous Ti-3Zr-2Sn-3Mo-25Nb (TLM) scaffolds, this study innovatively proposed the combination of additive manufacturing and electrochemical dealloying. The macro-scale pores of TLM were fabricated using selective laser melting (SLM), with a pore size of 640 μm and a porosity of 70.92 %. Then, a biphasic microstructure was obtained by heat treatment. Finally, the micro- and nano-scale structure was prepared via electrochemical dealloying. The elastic modulus of the multiscale hierarchical porous TLM scaffolds was 1.43 GPa, which closely matched the human bone tissue, indicating excellent biomechanical adaptation. Meanwhile, in vitro experiments further demonstrated that these scaffolds significantly enhanced BMSCs adhesion. The alkaline phosphatase (ALP) activity, calcium deposition, and collagen secretion were up-regulated, while lipid differentiation was down-regulated, indicating the scaffolds exhibited the potential for osseointegration. This research provides a valuable method for the preparation of multiscale hierarchical porous titanium scaffolds and offers innovative insights for the development of customized hard-tissue implants.